Padronização e aceitabilidade do licor de araçá-boi (Eugenia stipitata Mac Vaugh) - Silva, Everton Martins da (2021)
The araçá-boi (Eugenia stipitata ssp. Sororia Mcvaugh), is a native Amazonian species of great importance to the local economy. It has a rounded shape weighing from 30 to 800 grams. fresh consumption is limited because it is an acidic fruit. Its pulp has great potential in the agroindustry for the manufacture of concentrated juice, ice cream, sweets, jellies, liqueurs, etc. The main objective of the present work was the manufacture of araçá-boi liqueur, from that the testing of different dosages of araçá-boi pulp/alcoholic source, the evaluation of the maceration time, the quantification of different dosages of sugar and the acceptability of araçá-boi liqueurs tasted by people over 18 years of age. This research was carried out in the Food Technology laboratory at the Institute of Exact Sciences and Technology - ICET of the Federal University of Amazonas - UFAM, in which the liqueurs were divided into four formulations with different amounts of pulps/L of vodka at different concentrations of the fruit , all formulations underwent a 15-day maceration time and from this, the pH was investigated, sensory analysis, and submitted to analysis of variance (ANOVA) to compare the magnitude of the liqueur formulations using the SISVAR 5.8 and the comparison of means in which the Tukey test was used, at the level of 5% probability. The best results obtained from the experiment were the liqueurs that compose the formulations of 250g of sugar/L of water and 30g of sugar/L of water, in which samples 5, 15 and 16 were those containing 250g of sugar/L of water and sample 1 was 30g sugar/L water. So the attributes taste and purchase intention were the determining factors for choosing the best liquor treatment, where samples 1, 5, 15 and 16 are recommended and samples 12 and 13 are not recommended.